Scheimpflug versus optical coherence tomography to detect subclinical corneal edema in Fuchs endothelial corneal dystrophy - Augustin, Victor A.; Köppe, Maximilian; Son, Hyeck Soo; Meis, Jan; Yildirim, Timur Mert; Khoramnia, Ramin; Auffarth, Gerd U. (Cornea, 2022)
Purpose: - The purpose of this research was to compare the ability of Scheimpflug and anterior segment optical coherence tomography (OCT) in detecting subclinical corneal edema in patients with Fuchs endothelial corneal dystrophy (FECD) without clinical corneal edema. - Methods: - In this single-center, consecutive case series, 47 eyes of 29 patients with FECD were analyzed. The main outcome measures were anterior/posterior keratometry and central/thinnest corneal thickness. The criteria for subclinical corneal edema were loss of regular isopachs, displacement of the thinnest point of the cornea, and presence of posterior surface depression. Tomographic analyses were performed using Scheimpflug imaging (Pentacam HR) and OCT (anterior segment swept-source optical coherence tomography). - Results: - The measurement of the continuous variables revealed a significant difference between the 2 devices. The anterior curvature was steeper and the posterior curvature was flatter when measured with OCT (P < 0.001). The OCT showed a lower central corneal thickness and thinnest corneal thickness (P < 0.001). The agreement between both devices to detect subclinical corneal edema was high. The interdevice reliability for loss of parallel isopachs as measured by Cohen kappa coefficient was 0.84; for the displacement of the thinnest point of the cornea, it was 0.6, and for the focal posterior corneal surface depression, it was 0.62. Subclinical corneal edema was detected in 72.3% of the patients with both devices. In only 2 cases (4.3%), subclinical corneal edema was detected by one of the devices. - Conclusions: - Scheimpflug and OCT imaging were both able to detect tomographic patterns of subclinical corneal edema. Therefore, both devices can help decision-making, favoring early endothelial keratoplasty in symptomatic patients with FECD without clinical corneal edema.